2016
DOI: 10.3906/sag-1411-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the protective effects of vitamin K and vitamin A on the modulation of hypervitaminosis D3 short-term toxicity in adult albino rats

Abstract: Background/aim: Vitamin D 3 has increased risk of toxicity due to its common use in multivitamin preparations. Vitamin K and vitamin A play an important role in vitamin D action. The goal of the current study was to compare the protective effects of vitamin K and vitamin A on the modulation of hypervitaminosis D 3 toxicity in rats by assessing serum calcium, renal function tests, cardiac enzymes, and related histopathological changes.Materials and methods: Eighty adult albino rats were divided into four groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…The results also agree with Elshama et al (2016), they showed a signi icant increase in serum urea associated with a substantial decrease in serum creatinine that received vitamin D 3 in a toxic dose (2 mg/kg), in comparison with the control group. As well, they indicated that differences between the toxic dose of vitamin D 3 and the renal function tests of urea and creatinine in rats.…”
Section: Results Ofsupporting
confidence: 90%
See 1 more Smart Citation
“…The results also agree with Elshama et al (2016), they showed a signi icant increase in serum urea associated with a substantial decrease in serum creatinine that received vitamin D 3 in a toxic dose (2 mg/kg), in comparison with the control group. As well, they indicated that differences between the toxic dose of vitamin D 3 and the renal function tests of urea and creatinine in rats.…”
Section: Results Ofsupporting
confidence: 90%
“…More intake of vitamin D supplements by the general population and a growing number of prescriptions of therapeutic doses (included very high doses) without medical monitoring might result in a greater risk of exogenous hypervitaminosis D, with symptoms of hypercalcemia also known as vitamin D toxicity (Marcinowska-Suchowierska et al, 2018). Physicians also recommend a high daily dose of vitamin D 3 for many weeks as a treatment for chronic bone diseases (osteomalacia and osteoporosis) and autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and psoriasis because they are associated with low blood levels of vitamin D 3 metabolites; therefore, the incidence rate of hypervitaminosis D 3 may increase (Elshama et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A is necessary for vitamin D signalling but excessive intakes, common in developed countries, can antagonise vitamin D’s effects, perhaps through annexation of the retinoid X receptor (RXR) to form RXR:RAR complexes ( 75 ). Experimentally, vitamin D toxicity is mitigated by large doses of vitamin A and in humans supplemental vitamin A can abolish health benefits of vitamin D supplementation ( 76 , 77 ). Other interactions are reported for vitamin K (and possibly other vitamins) ( 78 ).…”
Section: Other Dietary Factors Modulating Vitamin D Efficacymentioning
confidence: 99%
“…Fetuses’ renal atrophy and degeneration of Malpighian corpuscles were also noted by Andrew ( 2007 ), Tawfik and Al-Badr ( 2012 ), Osman et al ( 2012 ), Elshama et al ( 2016 ), and AL-Khatawi et al ( 2019 ). Park et al ( 2000 ) and Beyreuther et al ( 2007 ) suggested that prenatal exposure to MSG would result in histological changes in the kidney because MSG readily crossed the placenta and accumulated in fetal tissue throughout gestation.…”
Section: Discussionmentioning
confidence: 61%